Coherence in popularized medico-pharmaceutical reports: The case of EPAR summaries for the public - Aage Hill-Madsen (Revista de Lenguas para Fines Específicos)
The present article investigates a particular lay-oriented medico-pharmaceutical genre, viz. the European Public Assessment Report – summary for the public, which is a summarized version of a much longer specialized report published by the European Medicines Agency. The specialized report sets out the results of the Agency’s evaluation of a given pharmaceutical company’s application for marketing authorization of a medicinal product in EU countries. The summary for the public reports the gist of the specialized source text in a linguistic register suitable for a lay readership. However, while the summaries are thus products of registerial adaptation, it is uncertain whether the rewriting results in texts that are sufficiently coherent, given that the key features of summary writing – condensation and selection of information – may be at odds with the production of coherent text. Therefore, based on an analytical methodology originating in Systemic-Functional Linguistics, this article investigates a small corpus of EPAR summaries to assess the level of coherence in these rewritten texts. The investigation uncovers the ways and the extent to which the summaries employ structural and non-structural cohesive devices to achieve coherence. It is concluded, however, that while the use of these devices in the texts is such as to create a clear potential for coherence, this potential is not adequately exploited, which means that the level of coherence in the texts leaves something to be desired.